Analysis of unused prescription opioids and benzodiazepines remaining after death among Medicare decedents. (1st February 2021) - Baum, Laura Van Metre; Bruzelius, Emilie; Kiang, Mathew V.; Humphreys, Keith; Basu, Sanjay; Baum, Aaron
Highlights: Millions of opioid and benzodiazepine prescriptions are dispensed near end-of-life. We estimate 1 in 5 Medicare decedents leave behind opioid or benzodiazepine pills. Ensuring safe disposal after death is an underappreciated public health need. Abstract: Background: Millions of opioid and benzodiazepine prescriptions are dispensed near end-of-life. After death, patients' unused prescription pills belong to family members, who often save rather than dispose of them. We sought to quantify this exposure in Medicare beneficiaries. Methods: We estimated the share of decedent Medicare beneficiaries who potentially left behind opioid or benzodiazepine pills at the time of death using Part D claims of a 20 % national sample of Medicare beneficiaries between 2006−2015 linked to the National Death Index. Results: We estimated that 1 in 6 Medicare beneficiaries who died between 2006−2015 potentially left behind opioid pills, and 1 in 10 who died between 2013−2015 potentially left benzodiazepines as well. Leftover pills were more common among younger, dually enrolled, and lower-income beneficiaries, as well as beneficiaries living in non-urban areas and those with a history of mental illness, drug use disorders, and chronic pain. North American Natives and Non-Hispanic Whites had higher proportions than Black, Hispanic, and Asian decedents. Conclusions: Opioids and benzodiazepines are commonly left behind at death. Policies and interventions that encourage comprehensive and safe medication disposal after death may reduce risk for intra-household diversion and misuse of prescription opioids and benzodiazepines.